Impact of the acceptor units on optoelectronic and photovoltaic properties of (XDADAD)n-type copolymers: Computational and experimental study. (February 2021) - Klimovich, Irina V.; Prudnov, Fedor A.; Mazaleva, Olga; Tukachev, Nikita V.; Akkuratov, Alexander V.; Martynov, Ilya V.; Peregudov, Alexander S.; Shestakov, Alexander F.; Zhugayevych, Andriy; Troshin, Pavel A.
Abstract: A series of ten conjugated polymers incorporating in their molecular frameworks extended DADAD building blocks with thiophene donor (D) and either benzotriazole, benzoxadiazole, benzothiadiazole, difluorobenzothiadiazole or quinoxaline acceptor (A) units were synthesized and characterized. The optoelectronic properties of new polymers were computed and experimentally investigated revealing a good relationship, which can guide further rational design of materials with tailored properties for organic photovoltaics using in-silico approaches. The performance of all polymers in organic bulk heterojunction solar cells was compared and some important empirical rules were formulated for reaching the best photovoltaic performance from (X-DADAD)n family of polymers. Graphical abstract: Image 1 Highlights: Conjugated polymers based on different acceptors have been synthesized. Weak acceptor units result in wider band gaps and lower parameters of solar cells. Good relationship between computed and experimental properties was revealed.